Use of MELD score in country with low organ donation - Somchai Limsrichamrern (2018)
Background: The model for end-stage liver disease (MELD) score was used to prioritize liver allocation in the USA that decreased the mortality in awaiting patients. The current national policy for liver allocation in Thailand is to offer organs to the transplant center, not directly to the patients themselves. The aim of the present study was to determine the accuracy of MELD score to predict the mortality of patients on liver transplantation waiting list in Thailand, a country with low organ donation. Material and Method: Between January 2006 and March 2007, we prospectively collected data of all patients on liver transplantation waiting list. MELD score was calculated. All patients were followed until they were transplanted, dead, or to the end of the present study. Patients were then divided into three groups (dead, alive, and transplanted) according to the outcome. Differences between groups were compared using Chi-square test. Results: Seventy-three patients were enrolled (male:female = 48:25). Mean age was 55.6 years. At the end of the study, 44 patients were alive (60.3%, MELD 8-31), 21 were dead (28.8%, MELD 15-40), and eight were transplanted (11%, MELD 12-30). The dead group was compared with alive group to determine mortality. Patients who died had higher MELD score than patients who were alive. Patients with MELD score more than 15 had significantly (p-value = 0.006) higher mortality than patients with MELD score of less than 15. Conclusion: MELD score is very useful in stratifying severity and mortality risk of cirrhotic patients while on liver transplant waiting list. A MELD score of 15 is associated with significantly increased mortality on awaiting patients. MELD score should be used to prioritize liver organ in order to save lives.